Protein Kinases in Copper Homeostasis: A Review on Cu+-ATPase Modulation - Rafael H.F. Valverde; Jennifer Lowe (2024)
Copper is an essential heavy metal for diverse biological functions but toxic in excess. Consequently, a tightly regulated protein system is required to ensure adequate intracellular levels. In recent decades, several studies have explored the role of Cu+-ATPases in copper transport and homeostasis, revealing that these proteins are subject to kinase-mediated phosphorylation that significantly impacts their function. Techniques such as phosphoproteomic screening, site-directed mutagenesis, and artificial neural network tools demonstrated the regulatory effect of phosphorylation on these ATPases. Different protein kinases regulate Cu+-ATPases, modulating the active copper transport by affecting specific steps of the catalytic cycle, long-range intramolecular crosstalks, protein trafficking, gene expression, and protein stability. Therefore, the regulatory phosphorylation of Cu+-ATPases by kinases ultimately influences the intracellular copper distribution. This study aims to present a review of the scientific literature on the regulation of Cu+-ATPases by kinase-mediated phosphorylation as a crucial mechanism for copper homeostasis. This regulation offers new perspectives for developing therapies for disorders related to copper metabolism, such as Wilson and Menkes diseases, as well as cancer, diabetes mellitus, Parkinson’s, and Alzheimer’s diseases. These findings emphasize the need to further comprehend the signaling pathways involving protein kinases in the context of copper regulation.